The Relationship of the Teachers’ Growth Mindset to the Students’Mutual Cooperation Character in Primary School - Yulianti, Made Dwi; Astawan, I Gede; Riastini, Putu Nanci (Indonesian Values and Character Education Journal, 2024)
The teacher's mindset will influence learning strategies such as designing or implementing learning. Furthermore, the strategies created by teachers will influence student character development. This research is motivated by the absence of other research that discusses the relationship between elementary school teachers' growth mindset and the cooperation character of elementary school students. This research aims to describe the growth mindset profile of elementary school teachers and find the relationship between elementary school teachers' growth mindset and students' cooperation character. The research was an ex post facto correlational design involving 30 elementary school teachers as research subjects. Data was collected through non-test methods, using questionnaires and checklist sheets. Data analysis used quantitative descriptive and single predictor regression analysis techniques. The research results show that most teachers have a growth mindset with some fixed ideas. A correlation coefficient of 0.769 was also obtained, meaning there is a strong and unidirectional relationship between the growth mindset of elementary school teachers and the students' cooperative character. This research implies that more training can be held to shape the growth mindset of teachers so that they can take more of a role in improving students' cooperative character.